(untitled) (Iranian Journal of Kidney Diseases, 2018)
Introduction. Early diagnosis of minimal change disease (MCD) is challenging in nephrotic children. CD80 is a protein expressed on the surface of podocytes associated with nephrotic syndrome and it is implicated in the induction of proteinuria. This study aimed to investigate the use of urinary CD80 for the diagnosis of MCD. Materials and Methods. Urinary CD80 levels were evaluated in 36 children with nephrotic syndrome and normal glomerular filtration rate. They were divided into three groups of MCD (n = 21), focal segmental glomerulosclerosis (n = 9), and other glomerulopathies (n = 6). The MCD group was subdivided into 2 of those with remission (n = 11) and those in the active stage (n = 10). Forty healthy children were included as controls. Results. The urinary CD80 level was significantly higher in the MCD group (3.5 ± 2.1 ng/mg creatinine) than in the focal segmental glomerulosclerosis group (1.2 ± 0.5 ng/mg creatinine, P < .001), the other glomerulopathies group (1.4 ± 0.7 ng/mg creatinine, P < .001), and the control group (0.7 ± 0.2 ng/mg creatinine, P < .001), while it showed no significant difference among the non-MCD groups. There was no significant difference between MCD in remission and MCD in relapse, either. A urinary CD80 cutoff value of 1.5 ng/gm creatinine showed a sensitivity of 100% and a specificity of 86% for diagnosis of MCD. Conclusions. Urinary CD80 levels were significantly higher in the children with MCD than in the controls and patients with other causes of nephrotic syndrome.